2014
DOI: 10.1111/trf.12926
|View full text |Cite
|
Sign up to set email alerts
|

Time course for the recovery of physical performance, blood hemoglobin, and ferritin content after blood donation

Abstract: The individual recovery was variable, but physical performance was recovered 14 days after a standard blood donation, despite blood Hb concentration remaining lower than at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 27 publications
9
33
0
Order By: Relevance
“…Despite these methodologic differences all of these studies found that a reduction in blood Hb (B‐Hb) impairs physical performance . Extending the findings by Burnley and colleagues and Judd and colleagues we observed that peak VO 2 and time trial (TT) performance were back to baseline 2 weeks after a standard blood donation of 450 mL of blood, whereas B‐Hb concentration was only returned to baseline after 4 weeks …”
supporting
confidence: 64%
“…Despite these methodologic differences all of these studies found that a reduction in blood Hb (B‐Hb) impairs physical performance . Extending the findings by Burnley and colleagues and Judd and colleagues we observed that peak VO 2 and time trial (TT) performance were back to baseline 2 weeks after a standard blood donation of 450 mL of blood, whereas B‐Hb concentration was only returned to baseline after 4 weeks …”
supporting
confidence: 64%
“…Hematocrit, hemoglobin concentration, hemoglobin mass, ferritin, iron, and RBC were all reduced after blood donation and their values were still lower than basal values after 4 weeks, except for iron and hemoglobin mass. We hereby confirm previous reports showing that recovery of hematological parameters may take a few weeks or even more [15–17]. Here, hematocrit, hemoglobin concentration, ferritin, and RBC were still lower 3 months after the first blood donation, at the time of beginning the second test series, indicating that the recovery of those parameters was incomplete before the next blood donation.…”
Section: Discussionsupporting
confidence: 90%
“…The largest reduction in maximal power output was 4% and in VO 2 peak 11%, which corresponds to values previously reported [15, 20, 22, 24]. Only one study extended the recovery period until 4 weeks [15].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations